Generic Pharmaceuticals- Review and Approval by COFEPRIS in Mexico - Rayhan Shahid Shanavas; Ridah Shaista Shanavas; Shaik Zakir Hussain; Ujwala Akunuri; Tatipalli Madhukar Reddy (International Journal of Pharma and Bio Sciences, 2024)
Mexico, the second largest pharmaceutical market in Latin America with a population of 200 million, faces increasing demand for generic drugs due to factors such as an aging population and the prevalence of non-communicable and communicable diseases. A mix of private, public, and out-of-pocket payment systems drives this demand. Access to medicines is facilitated by three key institutes: The Mexican Institute of Social Security, The Institute of Health and Social Services, and Seguro Popular. Despite approximately 200 pharmaceutical companies serving the market, limited competition among generic drug manufacturers and slow price erosion creates opportunities for foreign pharmaceutical players with diverse portfolios and growth potential. COFEPRIS, Mexico’s regulatory agency, oversees the evaluation and approval of all medicinal products for commercialization. While it accepts drugs approved in multiple regulated markets, entry into the Mexican market requires a nuanced approach, typically facilitated by a local agent in a phased manner. The approval process involves four steps for generics and five for new drugs, spanning 90 to 350 days, contingent upon submission quality and process specifics. The dossier comprises three modules, with the ongoing integration of changes to align approval processes with regulated markets and incorporate intellectual property considerations. This research reviews regulatory processes for international pharmaceutical companies, leveraging published literature and expert insights to provide a comprehensive roadmap for expedited approvals. Particularly beneficial for small companies seeking entry into Mexico with their own or licensed generic drugs, this guidance aims to enhance access to highquality, affordable medications for Mexican patients while expanding revenue opportunities for international pharmaceutical firms.